The Dominance of the ACE Gene Shapes According to Anaerobic Threshold for Players in Handball - Donnie Sabah Ali (Journal of Global Pharma Technology, 2016)
The current study aimed at identifying the shape s of the ACE gene and the laconic threshold. The researchers used descriptive research in a survey method to identify the majority of players who had a delay in reaching the genetic threshold according to the gene, as were identified shape s of dominant gene in the research sample which (DD, ID, II) has been the research sample and selected determine purposively they handball players for the team Muthanna province's 12 players have been divided according to shape s to (DD) and the number (5 ) players and (II) and the number (4) players, and finally (ID) and the number (3) players have been conducting a blood test for the withdrawal of a sample corresponding to the date on Monday, a brief summary (14 2 2018). The gene was detected in the sample, after which the gene shape s were detected to identify the differences between the groups through any group that was delayed to reach fatigue and the group with the genetic makeup (DD) was the most delayed to reach the anaerobic threshold where researchers attribute the genetic makeup (DD) is what distinguishes this group from others.Keywords: ACE gene and anaerobic threshold.